A USABILITY OF GRAPHIC DESIGN WITH LOCAL CONTENT IN THE INTERACTIVE MULTIMEDIA DESIGN FOR INDONESIAN STORYTELLING - Natadjaja, Listia (Nirmana, 2004)
As the computer becomes a trend%2C interactive multimedia design can be one media to communicate the cultural knowledge. A folktale can be a one of the powerful materials to show a countryÂ’s culture. The folktale content can be understood effectively by implementing some cultural information background. The main aim of using the local content is to give a vision of the richness culture through graphic design in interactive multimedia technology. By implementing local graphic design based on the cultural background%2C user can have different feeling about the graphic style and the Indonesian richness culture. This method can also help the user to understand the interactive multimedia content easily. Finally%2C graphic design with local content is very effective for a transferring the richness culture. In order to make a good interactive multimedia design content based on a cultural background%2C a designer should need to understand about users%2C culture%2C technology and the whole design process. Abstract in Bahasa Indonesia : Seiring dengan berkembangnya penggunaan komputer menjadi suatu trend%2C interaktif multimedia desain dapat menjadi suatu media untuk mengkomunikasikan suatu pengetahuan mengenai suatu kebudayaan. Cerita rakyat%2C dapat merupakan kekuatan untuk menunjukan budaya suatu negara. Isi dari suatu cerita rakyat dapat dimengerti secara efektif dengan implementasi beberapa latar belakang budaya. Tujuan utama dari penggunaan muatan lokal adalah untuk memberikan suatu visi tentang kekayaan budaya melalui desain grafis dalam teknologi interaktif multimedia. .Dengan mengimplementasikan desain grafis lokal berdasar pada latar belakang budaya%2C pengguna multimedia dapat mempunyai perasaan yang berbeda terhadap gaya desain dan kekayaan budaya Indonesia. Metode ini diharapkan juga dapat membantu pengguna untuk mengerti isi suatu interaktif multimedia secara mudah. Pada akhirnya%2C dapat dikatakan bahwa muatan lokal sangatlah bermanfaat untuk mentranfer pengetahuan tentang kekayaan budaya. Untuk membuat suatu muatan desain interaktif multimedia secara baik berdasar pada suatu latar belakang budaya%2C seorang desainer perlu mengerti tentang pengguna%2C kebudayaan%2C teknologi dan keseluruhan proses desain. design process%2C interactive multimedia%2C culture%2C technology.